2022
DOI: 10.3390/children9060863
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Values of Red Flags and a Clinical Prediction Score for Emergent Intracranial Lesions in Non-Traumatic Pediatric Headaches

Abstract: Introduction: Diagnosis of emergent intracranial lesions that require emergency treatment either medically or surgically in non-traumatic pediatric headaches is important. Red-flag signs and symptoms are commonly used as justification for neuroimaging; however, evidence on its diagnostic values is limited. The study aims to identify diagnostic values of red-flags and develop a clinical prediction score to help improve the diagnostic yield of neuroimaging. Methods: A retrospective review of 109 pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Headache is a common symptom in children, even in preschoolers and represents one of the main neurological causes of access to the ED. Headache in children under six years of age is still considered a diagnostic challenge often requiring neuroimaging to exclude malignant causes (15,16,(23)(24)(25)(26)(27)(28). To date, there are few studies focused on this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a common symptom in children, even in preschoolers and represents one of the main neurological causes of access to the ED. Headache in children under six years of age is still considered a diagnostic challenge often requiring neuroimaging to exclude malignant causes (15,16,(23)(24)(25)(26)(27)(28). To date, there are few studies focused on this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Among 109 children with nontraumatic headaches studied by Manoyana et al, 48 25.5% were diagnosed with brain tumor, 25.5% had intracranial infections, and 13.7% had intracranial hemorrhage. Among the children aged < 5 years, four out of six were diagnosed with brain cancer, albeit lacking statistical significance due to too few under-five-year-olds in the study.…”
Section: Introductionmentioning
confidence: 93%
“… 45 Rho et al, 47 observed that imaging for pediatric headaches, particularly recurring headaches, was quite common, with the most frequent group undergoing unnecessary imaging. Manoyana et al, 48 recently identified four red flag predictors for PM: an abrupt onset (< three months), altered consciousness, focal motor abnormality, and ocular/pupillary abnormality or squint. Children with nontraumatic headaches may benefit from clinical predictor scores based on these four red flags.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Medina et al [ 23 ], in a study of 315 children, the probability of brain tumors in patients with headaches for less than 6 months and at least one red flag was approximately 4% compared to 0.4% in those who had no red flag [ 23 ]. Red flags are presented in Table 3 [ 24 ].…”
Section: Red Flagsmentioning
confidence: 99%